Pengaruh Inovasi dan Kualitas Pelayanan terhadap Keunggulan Bersaing UMKM Pauwbili - Andrei Maryen; Edward Clan; Jenny Mardelin Kambu (Journal of Innovative and Creativity, 2025)
Establishing a continuously growing business capable of dominating the market is certainly the expectation of every entrepreneur. However, the increasing presence of competitors offering similar products has intensified business competition. In the midst of this growing competition, UMKM Pauwbili is required to take strategic measures to address these challenges by implementing product innovations and improving service quality in order to achieve competitive advantage. The purpose of this study is to determine whether innovation and service quality have an influence on competitive advantage. This research employs quantitative data with a sample of 40 customers of UMKM Pauwbili in Sorong City using a non-probability sampling method through purposive sampling. Data analysis was conducted using SPSS version 25. The results of this study indicate that: (1) Innovation has a significant influence on competitive advantage, (2) Service quality does not have a significant influence on competitive advantage, and (3) Innovation and service quality simultaneously influence competitive advantage.